Effects of obesity indices/GDM on the pregnancy outcomes in Chinese women: A retrospective cohort study - Song, Zhimin; Cheng, Yan; Li, Tingting; Fan, Yongfang; Zhang, Qingying; Cheng, Haidong (Frontiers in Endocrinology, 2022)
Objective To analyze pregnancy complications and outcomes of mothers with obesity or gestational diabetes mellitus (GDM). Methods 15065 mothers were categorized into four and three groups by pre-pregnancy body mass index (preBMI) and abdominal circumference (AC), respectively, or divided into GDM or non-GDM groups. Logistic regression analysis was utilized to identify independent factors associated with pregnancy complications and outcomes. Results The overweight and obesity groups accounted for 16.0% and 4.0% of the total population, respectively. GDM incidence rate was 12.3%. The overweight and obesity groups (pre-pregnancy body mass index [preBMI] ≥ 24 kg/m2) were at higher risks for GDM, hypertensive disorders of pregnancy (HDP), gestational proteinuria, postpartum hemorrhage, preterm delivery, fetal malformation or stillbirth, neonatal asphyxia, large for gestational age (LGA), shoulder dystocia, and increased cesarean section rate. Similar results were obtained with AC grouping. GDM pregnant women had higher risks of HDP, preterm delivery, small for gestational age (SGA), LGA, and increased cesarean section rate. Conclusion People with obesity had a higher risk of adverse pregnancy outcomes. The recommended preBMI is 19.2-22.7 kg/m2. The recommended AC at 11-13+6 gestational weeks is 74.0-84.0 cm, and that value in normal preBMI is 74.0-82.0 cm.